Treatment tolerability and outcomes in elderly patients with head and neck cancer. Issue 3 (8th December 2020) - Dickstein, Daniel R.; Egerman, Marc; Monrose, Erica; Varma, Achintya; Ozbek, Umut; Sharma, Sonam; Liu, Jerry T.; Gupta, Vishal; Posner, Marshall R.; Misiukiewicz, Krzysztof; Miles, Brett A.; Genden, Eric; et al.
Abstract: Purpose: The number of elderly patients with head and neck squamous cell carcinoma (HNSCC) continues to grow. Management of this cohort remains poorly defined. We investigated treatment tolerability and clinical outcomes in this underrepresented population. Methods: We identified patients aged ≥70 with nonrecurrent, nonmetastatic HNSCC treated curatively from 2007‐2018 and analyzed clinical covariates. Results: Two hundred and twenty patients with a median age of 75 (interquartile range:72‐80) were identified. Age and comorbidities were not correlated with toxicity ( P ≥ .05). Patients who experienced a treatment interruption had significantly greater weight loss ( P = .042) and worse overall survival (OS) ( P < .001), but not worse disease‐specific survival ( P = .45), or locoregional control ( P = .21). Conclusions: Treatment interruptions were associated with weight loss and worse OS, but not disease related outcomes, suggesting an interruption in the elderly may be a surrogate for another issue. In sum, our data should guide clinical trial design to benefit this growing, neglected cohort.